(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The people of Samar are heavily dependent on coastal resources for their livelihoods. This dependence underscores the pivotal role that coastal ecosystems play in supporting the local community’s well-being, especially as Samar bays are consistently confronted with periodic occurrences of red tide. Given the paramount importance of these resources to the people, understanding how they perceive and respond to red tide becomes imperative. This study investigates the social dimensions of red tide perception among Samareños to inform management strategies. A quantitative approach, employing a structured KBP scale was used to assess the level of knowledge, beliefs, and practices relative to red tide. The findings reveal a high level of scientific knowledge (mean: 4.36) among respondents, indicating their comprehensive understanding of various aspects associated with the phenomenon. However, misconceptions persist regarding the effectiveness of cooking seashells to reduce red tide potency. Participants also hold favorable beliefs (mean: 4.06), signifying positive perceptions related to red tide. In terms of practices, respondents exhibit a high level of vigilance with a mean rating of 4.21 during red tide events, refraining from consuming affected seafood and implementing measures to prevent waste disposal into water bodies, recognizing its association to its occurrences. While overall knowledge is high, the presence of misconceptions highlights the need for targeted education and environmental campaigns to correct misconceptions. These efforts will further enhance the community’s understanding of the importance of sustainable practices and management, contributing to the long-term health of coastal ecosystems and the well- being of the local populace. In support of sustainable development, collaboration between local authorities and policymakers with the communities may be encouraged to seamlessly integrate these practices into local governance and disaster preparedness efforts, acknowledging the community’s steadfast commitment to safety during red tide events.